CULTURE OF PATIENT SAFETY IN PRIMARY HEALTH CARE IN A LARGE MUNICIPALITY IN THE PERCEPTION OF WORKERS. - Louzada Macedo, Lilian; do Carmo Fernandez Lourenço Haddad, Maria; Rigo Silva, Ana Maria; Girotto, Edmarlon (Texto & Contexto Enfermagem, 2020)
Objective: to characterize patient safety according to the perception of primary health care workers in a large city in Paraná. Method: cross-sectional study, in which information was collected using the "Research on Patient Safety Culture for Primary Care" instrument, which was self-answered by health workers working in primary care, from April to June 2017. The Statistical Package for the Social Sciences program was used for data analysis. Results: it was found that as for the frequency of problems related to patient safety and quality of care, the "medical record/patient record being unavailable when needed" and "patient not getting an appointment within 48 hours was considered as a serious or acute problem". Regarding the support of managers/administrators/ leaders, the overall frequency of positive responses was only 38.4%. The section on global safety assessment showed the highest overall percentage of positive responses (79.0%). Workers in the southern region of the municipality under study had a worse assessment of the work process, communication, monitoring and manager support (45.5%, 61.6% and 29.3% of positive responses, respectively). Conclusion: it is concluded that there is a need to strengthen the culture of patient safety at this level of care, strengthening and valuing the performance of all workers, with the intensification of permanent education and the use of soft technologies.